2014
DOI: 10.1073/pnas.1404651111
|View full text |Cite
|
Sign up to set email alerts
|

Transcellular degradation of axonal mitochondria

Abstract: It is generally accepted that healthy cells degrade their own mitochondria. Here, we report that retinal ganglion cell axons of WT mice shed mitochondria at the optic nerve head (ONH), and that these mitochondria are internalized and degraded by adjacent astrocytes. EM demonstrates that mitochondria are shed through formation of large protrusions that originate from otherwise healthy axons. A virally introduced tandem fluorophore protein reporter of acidified mitochondria reveals that acidified axonal mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
461
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 519 publications
(474 citation statements)
references
References 27 publications
10
461
0
3
Order By: Relevance
“…Both phagocytosis and cell infiltration are implicated in glaucoma (5,41,64,65). Given the physiological function of ONH astrocytes in phagocytosing myelin and mitochondria, an early effect of high IOP may be to alter astrogliosis and disrupt phagocytosis (41,66). These functions are carried out when C3 effector fragments bind various receptors, including C3AR1 for C3a and CR1, CR2, CR3, and CR4 for C3b (67).…”
Section: Discussionmentioning
confidence: 99%
“…Both phagocytosis and cell infiltration are implicated in glaucoma (5,41,64,65). Given the physiological function of ONH astrocytes in phagocytosing myelin and mitochondria, an early effect of high IOP may be to alter astrogliosis and disrupt phagocytosis (41,66). These functions are carried out when C3 effector fragments bind various receptors, including C3AR1 for C3a and CR1, CR2, CR3, and CR4 for C3b (67).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the removal and degradation of mitochondria are tightly regulated [9,12,13], because dysfunctional mitochondria are a source of reactive oxygen species, which can damage the cell [14]. Deficits in mitochondrial trafficking have been proposed to contribute to the pathogenesis of Parkinson's disease, schizophrenia, amyotrophic lateral sclerosis, optic atrophy, and Alzheimer's disease [13,[15][16][17][18][19].…”
mentioning
confidence: 99%
“…This raises questions about intercellular mitochondrial transfer being involved in both replacement of defective organelles and recycling damaged organelles. In this context, a recent study showed that mitochondria from the optic nerve head are packaged into exosomes that are taken up and processed by surrounding astrocytes (35).…”
mentioning
confidence: 99%